Anti-IL-2 receptor antibodies as models for cancer therapy - Waldmann, Thomas (Henry Stewart Talks, 2007)
Structure and function of IL-2 receptor, Disorders of IL-2 receptor expression in disease, IL-2R alpha-directed monoclonal antibody mediated therapy of leukemia and autoimmune diseases, Anti-IL-2E alpha monoclonals armed with toxins or radionuclides, IL-15 and its use of the IL-/IL-15 beta receptor, IL-2/IL-15 R beta receptor directed therapy for leukemia and autoimmune diseases, The IL-2R alpha as a target in the elimination of CD4+ CD25+ T-regs (suppressor cells)
Archived at 2019/06/13